TiO2-photocatalytic transformation of Cr(VI) in the presence of EDTA: Comparison of different commercial photocatalysts and studies by Time Resolved Microwave Conductivity - Meichtry, Jorge Martin (2013)
The photocatalytic efficiency for Cr(VI) transformation in the presence of etilendiaminetetraacetic acid (EDTA) at pH 2 over various commercial TiO2 samples (Evonik P25, Cristal Global PC50, PC100 and PC500, Hombikat UV100, Fluka and Kemira S230) was evaluated. The decay was adjusted to a pseudo-first order kinetics in all cases and the photocatalytic activity of the samples was estimated from the kinetic constants. The order of the photocatalytic activity was PC500 ≅ UV100 > P25 ≅ PC100 > S230 ≅ PC50 ≫ Fluka and it strongly depends on the nature of the TiO2 samples, especially on the specific surface area, except for S230 and for P25. The formation of the Cr(III)–EDTA complex in solution as a product of the Cr(VI) photocatalytic reduction was confirmed by visible spectrophotometry. Simultaneous kinetics of Cr(VI) reduction and of Cr(III)–EDTA formation has been determined for the first time and the results indicate that evolution of both species are related. TRMC measurements were applied for the first time to a reductive heterogeneous photocatalytic reaction of a metal ion system, and the experimental results were adjusted to a power law decay, relating the data to those of the photocatalytic experiments.